2017
DOI: 10.1038/s41598-017-01386-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Plasma Extracellular Vesicle Characteristics and Internalization by Leukocytes

Abstract: Cells release lipid-bound extracellular vesicles (EVs; exosomes, microvesicles and apoptotic bodies) containing proteins, lipids and RNAs into the circulation. Vesicles mediate intercellular communication between both neighboring and distant cells. There is substantial interest in using EVs as biomarkers for age-related diseases including cancer, and neurodegenerative, metabolic and cardiovascular diseases. The majority of research focuses on identifying differences in EVs when comparing disease states and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
241
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(261 citation statements)
references
References 47 publications
13
241
7
Order By: Relevance
“…It will be important to investigate concentration and content changes in exosomes in age-related pathologies. A recent report showed that the concentration of extracellular vesicles (EV) from normal subjects decreased with aging [49]. Our data from controls showed no correlation; however, this discrepancy may due to the age of our controls, which spanned a relatively narrow range of middle age.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…It will be important to investigate concentration and content changes in exosomes in age-related pathologies. A recent report showed that the concentration of extracellular vesicles (EV) from normal subjects decreased with aging [49]. Our data from controls showed no correlation; however, this discrepancy may due to the age of our controls, which spanned a relatively narrow range of middle age.…”
Section: Discussioncontrasting
confidence: 74%
“…Despite the increased concentration, we observed a significant decrease in HMGB1 protein and trending decrease in NF-L and Aβ with age. A recent report on aging found that EV content might change with normal aging [49]. While the function of HMGB1 in brain is little understood, it appears that it can regulate DNA repair mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the levels of circulating EVs in plasma were shown to decrease in a cross-sectional and longitudinal study. Here it also was demonstrated that plasma EVs from older individuals had increased MHC-II expression on monocytes and were more readily internalized by B cells (72). This uptake of the plasma EVs results in activation of not only B cells, but also monocytes (72).…”
Section: Evs As Biomarkers Of Agingmentioning
confidence: 89%
“…Here it also was demonstrated that plasma EVs from older individuals had increased MHC-II expression on monocytes and were more readily internalized by B cells (72). This uptake of the plasma EVs results in activation of not only B cells, but also monocytes (72). Thus circulating EVs in aged individuals likely can modulate the immune response.…”
Section: Evs As Biomarkers Of Agingmentioning
confidence: 91%
“…In accordance, lower CD63 levels were here observed in plasma. Eitan et al [28] suggested that aging-induced decrease in circulating EVs is related to an increased internalization of vesicles into cells. On the other hand, our data could indicate increases in free IL-1β instead of package into exosomes, which might indicate different biological functions.…”
Section: Discussionmentioning
confidence: 99%